Urbanization predicts flight initiation distance in feral pigeons (Columba livia) across New York City. (August 2021) - Carlen, Elizabeth J.; Li, Richard; Winchell, Kristin M.
Abstract : Variation in behavioural traits is especially important in novel habitats where selection forces determine successful colonizers. Prey species must constantly balance the risk versus reward of remaining in an area with threats while gaining possible fitness benefits. Flight initiation distance, the distance at which an animal flees when approached by a human, is a common metric used to assess habituation to stressors and risk behaviour. Here we examine the flight initiation distance of 519 feral pigeons ( Columba livia ) across New York City, U.S.A. We examined this behavioural response across the metropolitan landscape with respect to multiple urbanization factors related to human activity, the abiotic environment and the ecological community. We used principal component analysis (PCA) to transform landcover characters and then liner models to test various anthropogenic variables including landcover, pedestrian traffic and human population size. We found that flight initiation distance in pigeons decreased with increased human activity (measured by pedestrian traffic and human population size) and more urban landcover (specifically longer road length and greater amounts of impervious surface). We also found that flight initiation distance was shorter in areas with more peregrine falcon, Falco peregrinus, sightings, but longer in areas with more red-tailed hawk, Buteo jamaicensis, sightings. Overall, this research demonstrates that feral pigeon behaviour varies with urbanization, human activity and ecological attributes. Since behavioural changes are often the most rapid phenotypic response to change, this study demonstrates that pigeons are responding to anthropogenic stressors, which may set the stage for adaptive changes. Highlights: Flight initiation distance in pigeons was lower in areas with higher urbanization. Pigeons allowed close approach in areas with increased human activity. Habitat heterogeneity influenced behavioural responses. Flight initiation distance was influenced by urban predator communities.